Research on Curriculum-based Ideological and Political Education with Foreign Language Courses: A Case Study of “Introduction to British and American Culture” - Zhong, Maobin (Pacific International Journal, 2025)
This study examines how curriculum-based ideological and political education (CPE) can be effectively integrated into the course Introduction to British and American Culture. Findings show that comparative curriculum design—highlighting China’s historical achievements, cultural values, and governance strengths alongside Western counterparts—has the potential to enhances students’ cultural confidence and ideological awareness. Innovative teaching strategies, including case studies of international events, multimedia tools, and guided group discussions, are identified as promising approaches to improve engagement and support students’ appreciation of China’s path, theory, system, and culture. While the study provides conceptual insights and instructional recommendations, it does not include empirical classroom data, which suggests the need for future field-based validation. The research offers practical guidance for aligning foreign language education with CPE goals and fostering students’ patriotism and cross-cultural competence.